PENGARUH OFFICE ATMOSFER DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. TELKOM AKSES KOTA BENGKULU - Agung Mulyana; Mimi Kurnia Nengsih (UM. Bengkulu, 2023)
This study aims to determine the effect of atmosphere and service quality on customer satisfaction at PT. Telkom Access Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the customers of PT. Telkom Access Bengkulu City, which is precisely located on Jl. Lt. Gen. Suprapto, No. 132, Kec. Ratu Samban, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 150 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that the atmosphere variable has a positive effect on customer satisfaction, service quality has a positive effect on customer satisfaction, and atmosphere and service quality together have a significant effect on customer satisfaction at PT. Telkom Access Bengkulu City. Keywords: Atmosphere, Service Quality, Customer Satisfaction